High Mortality Associated with Parainfluenza Virus Infection in Hospitalized Adults. (4th October 2017) - Hung, Ivan F. N; Li, Justin; To, Kelvin Kw; Tam, Anthony; Chan, Jasper Fw
Abstract: Background: Parainfluenza virus is a common cause of upper respiratory tract infections in adults. Nevertheless, its clinical characteristics and risk factors associated with mortality have not been well described. Methods: A retrospective analysis on a prospective cohort was conducted in a single centre in Hong Kong. We compared adult patients hospitalized for parainfluenza virus infection with those hospitalized for influenza infection during the same period. All recruited patients were follow-up for 1 year. Independent risk factors associated with mortality for parainfluenza virus infection were identified. Results: Between March 1, 2014 and February 28, 2015, a total of 1, 339 patients were recruited. Of these, 230 patients were hospitalized for parainfluenza virus infection and 1109 patients were hospitalized for influenza infection. Significantly more patients in the parainfluenza group were elderly home residents ( P = 0.003) and had a past medical history of cardiovascular diseases ( P < 0.001) and stroke ( P = 0.04). Patients in the parainfluenza virus group had significantly longer period from symptoms onset to hospital admission ( P < 0.001) and more symptoms of sputum production ( P = 0.03), chest wheeziness ( P < 0.001) and required oxygen support upon admission ( P < 0.001). Significantly more patients in the parainfluenza group developed secondary pneumonia, cardiovascular complication, and sepsis (all P < 0.001). Both the hospitalization days and frequency of admission are higher in the parainfluenza group ( P < 0.001). The 1-year mortality rate was significantly higher in the parainfluenza than the influenza group ( P < 0.001). Cardiovascular complication [OR: 1.8; 95% C.I. 1.01–3.20], invasive ventilation (OR: 12.7; 95% C.I. 2.63–61.50), and abnormal lymphocyte count upon admission (OR: 9.22; 95% C.I. 1.88–45.27) were independent risk factors associated with 1-year mortality in patients hospitalized for parainfluenza virus infection. Conclusion: Parainfluenza virus infection in the adults was associated with significantly higher mortality and longer hospitalization when compared with influenza virus infection. Patients with underlying cardiovascular diseases were particularly at risk. An effective vaccine and antiviral is very much needed. Disclosures: I. F. N. Hung, Pfizer: Scientific Advisor, Grant recipient and Speaker honorarium; Gilead: Scientific Advisor, Grant recipient and Speaker honorarium; MSD: Scientific Advisor, Grant recipient and Speaker honorarium; sanofi pasteur: Scientific Advisor, Grant recipient and Speaker honorarium; AstraZeneca: Scientific Advisor, Grant recipient and Speaker honorarium; J. F. Chan, Pfizer: Scientific Advisor, Grant recipient